Abnormal Aggregation and Increased Size of Platelets in Myeloproliferative Disorders - Cortelazzo, Sergio; Barbui, Tiziano; Bassan, Renato; Dim, Enrico (Thrombosis and Haemostasis, 1980)
Platelet aggregation is frequently impaired in myeloproliferative disorders (MPD). The presence of spontaneous platelet aggregation (SPA) or alterations of the aggregation pattern after ADP, epinephrine and collagen have been a frequent feature in the series of 52 patients here presented. The occurrence of SPA was not related to the findings obtained with the aggregating agents or to the number of circulating platelets. The aggregation results did not correlate with the number of megathrombocytes.The presence of platelet abnormalities, not completely corrected after busulfan therapy, and the increased size of platelets should aid in diagnosis of myeloproliferative disorders.
Keywords: Platelet aggregation; Myeloproliferative disorders; Platelet size; Platelet function after busulfan